Eine Architektur für Programmsynthese aus natürlicher Sprache (2016)
This book presents an architecture for programming in natural language called NLCI. It decouples the application domain from the text analyses: NLCI is an extensible architecture and its components are reusable. NLCI is evaluated with two case studies in two radically different domains: translating commands for a home automation system (openHAB) and generating 3D animations from English scripts with Alice.